DEVELOPMENT OF A HEALTH EDUCATION MATERIAL ON CHILD MEDIA HABITS - Arumugam, Catherine; Nik Farid, Nik Daliana; Said, Mas Ayu; Lourudusamy, Annie Patricia (Malaysian Journal of Public Health Medicine, 2026)
Early exposure to electronic devices and excessive screen time have shown to be disrupting young children’s emotional regulation, and delay their developmental milestone attainment. Hence, it is vital to ensure that parents are informed on practical ways of cultivating healthy child media habits. This study aimed to develop and validate an education material which would serve as guidance to lead an image-based communication to promote healthy child media habits to parents with children under five-years old. The single-paged education material in the form of a flyer was developed based on guidelines and evidence-based recommendations on usage of screen-based media among young children in Bahasa Melayu - the national language of Malaysia. It was validated using the ‘Patient Education Material Assessment Tool’ (PEMAT) guidelines by seven experts from the related fields, namely Public Health Medicine, Developmental Paediatrics, Family Medicine, Educational Psychology, Social Behavioural Science, and Health Communication. Based on the feedback given by the experts, the flyer underwent three rounds of iterations. Both the components of PEMAT’s scoring were good, with understandability reporting an average score of 89.7% and actionability reporting an average score 88.6%. The health education material named “MEDIA” – an acronym which denotes the five components of healthy child media habit is an excellent tool for health promotion in the field of technology and toddlers. This development of a health communication material tailored to local population in this study has contributed to the efforts of ensuring young children thrive in a safe media environment.